2020
DOI: 10.3126/jcmsn.v16i2.25652
|View full text |Cite
|
Sign up to set email alerts
|

Status of Anemia among Undergraduate Students of a Medical College of Central Nepal

Abstract: Background: Anemia is a public health concern with adverse health consequences. The vast nature of medical curriculum demands rigorous efforts and stress putting health science students at risk of anemia. In the present study, we aim to estimate the hemoglobin level of undergraduate health science students at Chitwan Medical College. Methods: This cross-sectional study included all 386 year I and II undergraduate health science students enrolled at Chitwan Medical College. An informed consent was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
1
1
Order By: Relevance
“…In the present study, the prevalence of anemia was found to be 38.7%, with female predominance (57.8% vs 14.9%). Similar prevalence of anemia (37.8%) was shown in a study conducted by Timilsina et al at a medical college in Nepal 15 . In another study done by Khakurel et al, 43.5% undergraduate medical students were found to be anemic 16 .…”
Section: Resultssupporting
confidence: 86%
“…In the present study, the prevalence of anemia was found to be 38.7%, with female predominance (57.8% vs 14.9%). Similar prevalence of anemia (37.8%) was shown in a study conducted by Timilsina et al at a medical college in Nepal 15 . In another study done by Khakurel et al, 43.5% undergraduate medical students were found to be anemic 16 .…”
Section: Resultssupporting
confidence: 86%
“…Moreover, the percentage of anaemia in the present study was 51⋅6 % which is lower than that reported from several low-income countries, such as India (80) , Ethiopia (97)(98)(99) , Nepal (100) , Brazil (101) and Latin America (77) however, is almost similar to that reported from high-income countries like Canada (102) and the United States of America (103) .…”
Section: Discussioncontrasting
confidence: 67%
“…Medical students' knowledge, attitudes, and practice towards thalassemia are likely to be shaped by various factors, including their academic and personal backgrounds, their exposure to patients with thalassemia, and their understanding of the social and cultural contexts in which the disease occurs. Medical students who look physically ft may not even know their status as anemia and carriers of thalassemia traits [13][14][15][16]. A study in Malaysia involving 400 undergraduate medical students has reported that 14.5% students had hypochromic microcytic red cell indices, 11% showed thalassemia red cell indices, and only 3.5% had iron defciency (IDA) red cell index which were fnally confrmed by serum iron/TIBC analysis [17].…”
Section: Introductionmentioning
confidence: 99%